2012
DOI: 10.1007/s10853-012-6523-y
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ag–Fe-decorated single-walled carbon nanotubes by arc discharge and their antibacterial effect

Abstract: A simple one-step approach for the preparation of Ag-Fe-decorated single-walled carbon nanotubes (AgFe/SWCNTs) by DC hydrogen arc discharge is presented in this article. The growth of SWCNTs and the attachment of Ag and Fe nanoparticles to the SWCNTs occur simultaneously during the arc discharge evaporation process. It has been confirmed that the Ag and Fe nanoparticles in the diameter range of 1-10 nm are well dispersed and tightly attached to the outer surfaces of SWCNTs. The as-grown Ag-Fe/SWCNTs have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“… ND [ 99 ] PVP-coated silver nanoparticles - 30−50 nm HIV-1 PVP-coated AgNPs Inhibited cell-associated HIV-1 and cell-free HIV-1 transmission. PVP-coated AgNPs were non toxic to cells explant [ 100 ] mercaptoethane sulfonate (MES)-coated silver and gold nanoparticles - 4 nm Herpes simplex virus type 1 (HSV-1) The MES-coated silver and gold nanoparticles inhibited HSV-1 infection in cell culture The MES-coated silver and gold were non toxic to host cells [ 101 ] PVP-coated silver nanoparticles - 69 nm +/− 3 nm Respiratory syncytial virus (RSV) Inhibited RSV infection showed low toxicity to cells [ 102 ] AgNP and polysaccharide-coated AgNP - 10−80 nm Monkey pox virus (MPV) The AgNPs of approximately 10 nm inhibit MPV infection in vitro, as an anti-viral Non of te GgNPs were cytotoxic (Vero cell monolayer sloughing) [ 103 ] AgNPs - 10−50 nm Hepatitis B virus (HBV) AgNPs inhibited in vitro HBV RNA and extracellular virions ND [ 104 ] AgNPs and polysaccharide-coated AgNP - 10 nm Tacaribe virus (TCRV) AgNPs inhibited the TCRV infection in vitro ND [ 105 ] Ag-NPs-coated PUC High resolution Scanning Electron Microscopy (HrSEM), UV Spectra 30–60 nm E. coli , S. aureus , M. luteus , K. pneumoniae , and Candida tropicalis , Candida krusei , Candida glabrata , and Candida albicans and HIV-1 Ag-NPs-coated PUC with HIV-1 and HSV-1/2 was able to inactivate their infectiousness as well as bacterial and fungal species ND [ 25 ] Mycosynthesized silver nanoparticles UV spectra, TEM, Nanosight-LM 20; 4−...…”
Section: Broad Spectrum Nanoparticle-antimicrobial Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“… ND [ 99 ] PVP-coated silver nanoparticles - 30−50 nm HIV-1 PVP-coated AgNPs Inhibited cell-associated HIV-1 and cell-free HIV-1 transmission. PVP-coated AgNPs were non toxic to cells explant [ 100 ] mercaptoethane sulfonate (MES)-coated silver and gold nanoparticles - 4 nm Herpes simplex virus type 1 (HSV-1) The MES-coated silver and gold nanoparticles inhibited HSV-1 infection in cell culture The MES-coated silver and gold were non toxic to host cells [ 101 ] PVP-coated silver nanoparticles - 69 nm +/− 3 nm Respiratory syncytial virus (RSV) Inhibited RSV infection showed low toxicity to cells [ 102 ] AgNP and polysaccharide-coated AgNP - 10−80 nm Monkey pox virus (MPV) The AgNPs of approximately 10 nm inhibit MPV infection in vitro, as an anti-viral Non of te GgNPs were cytotoxic (Vero cell monolayer sloughing) [ 103 ] AgNPs - 10−50 nm Hepatitis B virus (HBV) AgNPs inhibited in vitro HBV RNA and extracellular virions ND [ 104 ] AgNPs and polysaccharide-coated AgNP - 10 nm Tacaribe virus (TCRV) AgNPs inhibited the TCRV infection in vitro ND [ 105 ] Ag-NPs-coated PUC High resolution Scanning Electron Microscopy (HrSEM), UV Spectra 30–60 nm E. coli , S. aureus , M. luteus , K. pneumoniae , and Candida tropicalis , Candida krusei , Candida glabrata , and Candida albicans and HIV-1 Ag-NPs-coated PUC with HIV-1 and HSV-1/2 was able to inactivate their infectiousness as well as bacterial and fungal species ND [ 25 ] Mycosynthesized silver nanoparticles UV spectra, TEM, Nanosight-LM 20; 4−...…”
Section: Broad Spectrum Nanoparticle-antimicrobial Agentsmentioning
confidence: 99%
“… Purified Ag–Fe/SWCNT hybrid nanoparticles were effective against E. coli. ND [ 104 ] SWCNTs combine with H 2 O 2 or NaOCl TEM, SEM-EDX SWCNTs 1–1.5 nm Bacillus anthracis Spores The combined effect of SWCNTs and H 2 O 2 or NaOCl exhibited sporicidal effect on B. anthracis spores ND [ 87 ] SWNT/PLL/PGA Uv spectra, TEM, SEM, Quartz crystal microgravimetry SWNT is 0.8–1.2 nm E. coli and S. epidermidis SWNT/PLL/PGA highly inactivated E. coli and S. epidermidi s ND [ 28 ] Zirconia (ZrO2) nanoparticles SEM, EDX, AFM, U vis spectra, FTIR 50e100 nm, average size 50 nm Staphylococcus aureus, Escherichia coli, Candida albicans, Aspergillus niger Zirconia (ZrO2) nanoparticles exhibited antifungal and antibacterial against the test organisms. ND [ 111 ] Au/CuS core/shell nanoparticles (NPs) HRTEM, SEM, energy dispersive X-ray spectroscopy (EDS) 2–5 nm.…”
Section: Broad Spectrum Nanoparticle-antimicrobial Agentsmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Recently, photothermal therapy (PTT) has been proposed as a promising approach for killing bacteria. 10,[13][14][15][16][17][18][19][20][21][22] In the technique, photoabsorbing agents are delivered to target bacteria and irradiated with an appropriate light. The absorbed optical energy is then converted into heat, which results in irreparable physical damage and subsequent bacterial death.…”
Section: Introductionmentioning
confidence: 99%
“…Both CNTs and graphene own similar or even identical properties, including antibacterial activities and photothermal features. Photothermal therapy based on CNTs has been extensively investigated for drug delivery, cancer treatment, and antibacterial therapy. , Recently, graphene-based NMs conjugated with NIR irradiation have been applied for anticancer treatments and drug delivery. , Markovic et al demonstrated that graphene has better photothermal abilities than CNTs . Graphene nanowalls deposited on stainless steel substrates were able to damage the membrane of gram-positive S.…”
mentioning
confidence: 99%